Rapid and solvent-saving liquefaction of woody biomass using microwave–ultrasonic assisted technology. (January 2016) - Lu, Zexiang; Wu, Zhengguo; Fan, Liwei; Zhang, Hui; Liao, Yiqiang; Zheng, Deyong; Wang, Siqun
Graphical abstract: Highlights: Biomass liquefaction with microwave–ultrasonic assisted was first investigated. The heat and mass transfer were intensified by microwave and ultrasonic wave. The liquefaction yield of fir sawdust reached 91% under the optimal conditions. The liquefaction time was shortened to 20 min and the solvent dosage was halved. The assistive technology shows great potential in the field of biomass conversion. Abstract: A novel process to rapidly liquefy sawdust using reduced quantities of solvent, was successfully carried out via microwave–ultrasonic assisted technology (MUAT) in a sulphuric acid/polyethylene glycol 400-glycerol catalytic system. The influences of some key parameters on the liquefaction yield were investigated. The results showed that compared with traditional liquefaction, the introduction of MUAT allowed the solvent dosage to be halved and shortened the liquefaction time from 60 to 20 min. The liquefaction yield reached 91% under the optimal conditions. However, the influence on the yield of some parameters such as catalyst concentration, was similar to that of traditional liquefaction, indicating that the application of MUAT possibly only intensified heat and mass transfer rather than altering either the degradation mechanism or pathway. The introduction of MUAT as a process intensification technology has good industrial application potential for woody biomass liquefaction.